The Betz limit and the corresponding thermodynamic limit. Issue 2 (April 2023) - Coelho, Paulo
The Betz's limit for the maximum efficiency of an ideal wind turbine imposes a maximum value of about 60% on the conversion of the kinetic energy of an airflow into work. In this paper, we analyze the reason for this value because, from a thermodynamic point of view, it can be 100%. The present work explains the reason for this difference, since it appears to be relevant from a didactic point of view. However, from a practical point of view, the Betz's limit does not affect in any way the more useful and widespread expression for calculating the ideal maximum power of a wind turbine, which is at the origin of the referred limit. Complementarily, two approaches for the calculation of the theoretical maximum efficiency, in line with thermodynamics, are also presented in this work.